Influential Factors Shaping Retailer Behavior Considering Partnership With Producers (Case Study in Central Java, Indonesia) - Mayang Sari Marchainy; Harianto; Yudha Heryawan Asnawi (Business Review and Case Studies, 2024)
This research explored the dynamics of agricultural cultivation in Indonesia, where vast rural areas, distant from urban centers, necessitated robust distribution channels involving distributors and retailers to expand the market for pesticide products. Given the limited information on business interactions between producers and retailers and their implications on product market development, this study sought to evaluate the factors influencing retail behavior when considering partnerships with producers. Employing the PLS-SEM analysis method, we examined the influence of exogenous variables such as capital on endogenous variables like repurchase decisions, incentive programs, collaborative relationships, supply chain management, partnership decisions, and commitment. This investigation involved 53 retailers in the Central Java region and utilized 21 reflective indicators measured through questionnaires. The findings revealed significant relationships among variables, with the exception of the link between collaboration and partnership decisions, as well as partnership decisions and commitment. This indicated that the retailer-producer relationship hinged on business sustainability not yet to the level of product commitment. The implications suggested that producers could strategically utilize supply chain management and incentive programs to foster partnerships with retailers. Keywords: distribution channels, pesticide market, retail behavior, retail-producers partnership, supply-chain management